THE IMPACT OF TAX INCENTIVES, INFLATION AND GDP ON FOREIGN DIRECT INVESTMENT IN INDONESIA: A POST – IMPLEMENTATION ANALYSIS OF THE JOB CREATION LAW IMPLEMENTATION No. 11/2020 - Putry Sally Angellyta; Sri Setia Ningsih; Yanti Budi Asih; Erion (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2025)
This study investigates the impact of tax incentives, inflation, and Gross Domestic Product (GDP) on Foreign Direct Investment (FDI) in Indonesia following the implementation of the Job Creation Law No. 11 of 2020. The research seeks to determine whether these macroeconomic indicators significantly affect FDI inflows in the context of investment oriented regulatory reforms. Employing a quantitative research method, the study uses annual secondary data from 2019 to 2023 sourced from authoritative institutions, including the Indonesia Investment Coordinating Board (BKPM), Central Bureau of Statistics (BPS), Ministry of Finance, Bank Indonesia, and the Directorate General of Taxes. To examine the relationships among the variables, multiple linear regression analysis was conducted using SPSS. The empirical results show that although tax incentives have contributed to stabilizing investment growth in the early stages, their effect on FDI is not statistically significant. This implies that non fiscal determinants such as legal certainty, infrastructure quality, and regulatory consistency play a more substantial role in attracting foreign investors. The analysis also reveals a weak positive association between inflation and FDI, suggesting that inflation alone does not meaningfully influence investment decisions; instead, factors like interest and exchange rates may carry more weight. Additionally, GDP shows an insignificant effect on FDI, indicating that economic growth by itself is insufficient to stimulate foreign capital inflows. Notably, the post-reform period witnessed a notable increase in FDI, implying that comprehensive regulatory adjustments, rather than fiscal policy changes alone, were the primary drivers of investment growth, highlighting the need for an integrated investment strategy.